Strategies to achieve high productivity, high conversion, and high yield in yeast fermentation of algal biomass hydrolysate. Issue 3 (10th November 2021) - Huang, Xing‐Feng; Reardon, Kenneth F.
Abstract: The conversion of carbohydrates in biomass via fermentation is an important component of an overall strategy to decarbonize the production of fuels and chemicals. Owing to the cost and resources required to produce biomass hydrolysates, the economic and environmental sustainability of these fermentation processes requires that they operate with high yields, sugar conversion, and productivity. Immobilized‐cell technology in a continuous bioprocess can achieve significantly higher volumetric productivities than is possible from standard batch fermentation using free cells. Here, we demonstrate approaches for improvement of ethanol yield from algal hydrolysates and a mock hydrolysate medium. Saccharomyces cerevisiae was immobilized in alginate and incorporated into a two‐column immobilized cell reactor system. Furthermore, the yeast quorum‐sensing molecule, 2‐phenylethanol, was added to improve ethanol yield by restricting growth and diverting sugar to ethanol. The bioreactor system could achieve high ethanol volumetric productivity (>20 g/Lreactor ·h) and high glucose conversion (>99%) in mock hydrolysate, while the addition of 0.2% 2‐phenylethanol resulted in 4.9% higher ethanol yield. With an algal hydrolysate of <10 g/L sugar, the ethanol volumetric productivity reached 9.8 g/Lreactor ·h, and the addition of 0.2% 2‐phenylethanol increased the ethanol yield by up to 7.4%. These results demonstrate the feasibility of novel strategies to achieve sustainability goals in biomass conversions.